ALA LAMPUNG RASA PALEMBANG: STRATEGI PEMASARAN “PEMPEK TARISA” HALAL - Haque, Marissa Grace (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Pempek is very synonymous with Palembang, it is said that it was first sold by Chinese traders in 1916 in Palembang. However, with the large diaspora of Palembang people nationally and internationally, Lampung is now also producing Pempek with flavors that are very competitive with the original producing city in Palembang. The research uses a mixed-method, with descriptive analysis to determine the existence of the company's survival ability